(untitled) (Research, Society and Development, 2020)
The aim of the present study was to list the phytochemical components described in the literature of different extracts of Terminalia catappa leaves, describing those that have an antibacterial effect, as well as to evaluate evidence of the effectiveness of their antibacterial activity against strains of Staphylococcus aureus. It is an integrative review study and the research was carried out in the MEDLINE-Pubmed, SciELO and Google Scholar databases with the descriptors Terminalia catappa, Phytochemical composition and Staphylococcus aureus. A total of 9 articles published between 2015 and 2020, with full text and language in Portuguese and English, were selected. The results demonstrate that phytochemical components such as tannins, flavonoids, triterpenes, phenols and alkaloids were the most commonly found in the different extracts of T. catappa leaves. These components are responsible for a series of therapeutic effects, in particular the antibacterial effect, which is detected in tannins, flavonoids, saponins and alkaloids. In addition, there was significant efficacy in relation to the antibacterial activity of extracts of T. catappa leaves against strains of S. aureus (ATCC 25923) and methicillin-resistant S. aureus - MRSA (343602). Therefore, it is concluded that the leaves of T. catappa have a great potential to be used in the treatment of infectious diseases caused by S. aureus.